Pengaruh Motivasi Serta Stimulus Yang Menciptakan Persepsi Nasabah Terhadap Keputusan Memilih Layanan BRI Prioritas (Studi di Bank BRI Kantor Cabang Malang Martadinata) - Tragedy A, Rachman; mijati, Noermijati (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to determine, test, and analyze the influence of motivation and stimulus that creates the perception of consumers towards the decision of selecting Priority BRI services. This research was conducted at the Branch Office BRI Malang Martadinata. The population of this research is all the customers who have had service priority BRI amounted to 102 customers with samples taken at 50 clients because the samples are in the range of study while others are difficult to reach. Data are collected directly from respondents using a questionnaire research instruments. The method of data analysis used is multiple linear regression analysis. The results of this study indicate that the two variables, motivation and stimuli that create perceptions significantly influence customer decisions. This is shown by the results of the t test of the two variables that have a value of t, respectively 3,700 and 2,762. Motivation variable is the dominant variable influencing customer decisions in selecting Priority BRI service. It is shown from the largest standardized coefficient alpha than perception variables Keywords: Motivation, Stimuli, Perception, Customer Decision.